Quality assessment of Urochloa (syn. Brachiaria) seeds produced in Cameroon - Njehoya Clémence-Aggy (Nature Portfolio, 2021)
Abstract Urochloa (syn. Brachiaria) is the most popular fodder of livestock farmers in Cameroon for hay and seed productions. Farmers in Cameroon have been producing Brachiaria seeds for decades for own uses and surplus are sold to neighbours, and to traders from Cameroon and neighbouring countries. However, there is no information available about qualities of these seeds. Fifteen Urochloa seeds samples were collected from farmers and/or government stations in five regions (Adamaoua, East, North, North West, and West) and analysed for major seed quality parameters along with seeds of improved Urochloa cultivar Basilisk imported from Brazil as a check. Study showed significant differences among treatments for various seed quality parameters tested (P < 0.0001). The highest thousand grains weight was recorded in Basilisk (5.685 g), followed by W12 (3.555 g), A05 (3.153 g) and N01 (2.655 g). Caryopsis number and caryopsis weight were highest in Basilisk followed by E09, A06, and W12. Of three conditions tested for seed germination, mean germination was the highest in greenhouse (7.39%) where Basilisk had the highest germination (25.5%) followed by N01 (18.50%), A05 (14.50%) and W12 (12.75%). The seed viability ranged from 18% (E09) to 81% (N01), and there were a positive and highly significant relationships between seed germination and viability traits (r = 0.883; P < 0.0001). This study showed a marked difference in seed quality parameters of Urochloa grass seeds produced in Cameroon, and the potential of developing Urochloa grass seed business in the Northern, Adamaoua and Western regions of Cameroon.